Young Adult Romantic Couples' Conflict Resolution and Satisfaction Varies with Partner's Attention–Deficit/Hyperactivity Disorder Type. (25th April 2013) - Canu, Will H.; Tabor, Lindsey S.; Michael, Kurt D.; Bazzini, Doris G.; Elmore, Alexis L.
<x xml:space="preserve">Abstract</x> Attention‐deficit/hyperactivity disorder (ADHD) has previously been associated with less satisfaction and success in romantic relationships. This study compares conflict resolution and problem‐solving behaviors in young adult romantic couples either having one partner with ADHD combined type (C‐couples), having one partner identified with ADHD inattentive type (IA‐couples), or in which neither partner has an ADHD diagnosis (nondiagnosed [ND] couples). Self‐reports of current and childhood ADHD symptoms corroborated diagnostic status and speaker and listener behaviors, coded via the Rapid Couples Interaction Scoring System (Gottman, 1996), were the primary dependent variables. Analyses revealed greater negativity and less positivity in C‐couples' behavior during a conflict resolution task, relative to IA and ND couples, and this corresponded with couples' relational satisfaction. IA‐couples emitted relational behavior that was largely similar to ND couples. Findings support that relational impairment exists in C‐couples, and to some degree, contrast with previous research suggesting that individuals with predominant inattention experience greater social impairment in adulthood than those with other types of ADHD.